2021
DOI: 10.21037/jtd-21-1254
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to surveillance imaging adherence in early-staged lung cancer

Abstract: Background: Frequency of post-treatment surveillance is highly variable following curative resection of non-small cell lung cancer (NSCLC). We sought to characterize surveillance practices after lobectomy for early-stage NSCLC and to identify the impact of various demographic factors on patterns of surveillance. Methods: We included patients who underwent anatomic lobectomy for pathologic stage I NSCLC from 2007-2017. Demographic characteristics, post-operative imaging studies (internal and external), and trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, regionalization of care may come at a price 13–19 . Patients who must travel long distances to high‐volume, regional referral centers for surgery are unlikely to receive surgery if they are unable or unwilling to travel—in this study, rural patients treated close to home (<4.4 miles, the lowest quintile), were less likely to receive surgery than their metropolitan counterparts.…”
Section: Discussionmentioning
confidence: 74%
“…However, regionalization of care may come at a price 13–19 . Patients who must travel long distances to high‐volume, regional referral centers for surgery are unlikely to receive surgery if they are unable or unwilling to travel—in this study, rural patients treated close to home (<4.4 miles, the lowest quintile), were less likely to receive surgery than their metropolitan counterparts.…”
Section: Discussionmentioning
confidence: 74%
“…However, according to Erb et al, the adherence to available guidelines for surveillance was poor: fewer than twothirds of patients received recommended imaging, and almost 30% received non-recommended PET scans (74). Previous evidence also showed that over a third of the 1,200 patients who underwent lobectomy for pathologic stage I NSCLC, received minimal expected imaging studies for surveillance in the first five years after surgery (75).…”
Section: Surveillance and Treatment Responsementioning
confidence: 99%
“… 4 Within our cohort, travel distance was similarly shown to have a detrimental impact on the likelihood of undergoing appropriate postoperative therapy. We selected a threshold of travel >100 miles based on previous work by Bostock and colleagues, 5 which revealed the negative impact of travel distance on adherence to recommended postoperative surveillance imaging in NSCLC, and found that traveling >100 miles also led to substantially reduced likelihood of receiving indicated adjuvant surveillance (odds ratio, 0.13; 95% confidence interval, 0.06-0.26, P < .001). 4 …”
mentioning
confidence: 99%